Open Repair of a 12-cm Posttraumatic Aneurysm of Right Subclavian Artery - Tigkiropoulos, Konstantinos; Chalvatzoulis, Omiros; Chalvatzoulis, Eleftherios; Stavridis, Kyriakos; Karamanos, Dimitrios; Lazaridis, Ioannis; Efstathiou, Andreas; Saratzis, Nikolaos (Frontiers in Surgery, 2017)
Purpose: To present a rare case of a patient with a 12cm posttraumatic right subclavian artery aneurysm who was successfully treated by aneurysmatectomy and innominate-axillary bypass. Case Report: A 54-years old man presented to the emergency department due to progressive dyspnea and hoarseness of voice. His medical record was unremarkable except from a car accident 16 years ago suffering from right pneumothorax and multiple rib fractures. A chest x-ray revealed a mass in the upper lobe of the right lung and the patient was hospitalized for further investigation. A computed tomography (CT) of thorax with intravenous contrast was performed which depicted a giant aneurysm of right subclavian aneurysm. A surgical operation was scheduled by vascular and cardiothoracic surgeons. Aneurysmatectomy and innominate to axillary bypass was performed by a team of cardiac and vascular surgeons. The patient had an uncomplicated progress and was discharged on 5 days under a single antiplatelet therapy and symptom free. Conclusion: Posttraumatic subclavian artery aneurysm is a rare entity. Imaging is essential in diagnosis and planning of the disease. Open repair remains the goldstandard therapy despite evolution in endovascular surgery in such huge aneurysms.